(untitled) (Revista Latino-Americana de Enfermagem, 2014)
OBJECTIVES: to develop and assess a learning object about intramuscular medication administration for nursing undergraduates and nurses. METHOD: a random, intentional and non-probabilistic sample was selected of nurses from a Brazilian social network of nursing and students from the Undergraduate Program at the University of São Paulo School of Nursing to serve as research subjects and assess the object. RESULTS: the participants, 8 nurses and 8 students, studied the object and answered an assessment instrument that included the following criteria: educational aspects (relevance of the theme, objectives and texts/hypertexts), interface of the environment (navigation, accessibility and screen design) and didactic resources (interactivity and presentation of resources). In total, 128 significant answers were obtained, 124 (97%) of which were positive, assessed as excellent and satisfactory, considered as a flexible, dynamic, objective resources that is appropriate to the nursing learning process. CONCLUSION: the educational technology shows a clear and easily understandable language and the teaching method could be applied in other themes, contributing to the education and training of nursing professionals, positively affecting nursing teaching, stimulating the knowledge, autonomous and independent learning, aligned with the new professional education requirements.